Reproductive allocation of Solidago canadensis L. plays a key role in its invasiveness across a gradient of invasion degrees. Issue 4 (21st June 2021) - Cheng, Huiyuan; Wang, Shu; Wei, Mei; Wu, Bingde; Du, Daolin; Wang, Congyan
Abstract: Reproductive allocation (RA) plays a vital role in the development of ecological strategies during the life cycle of plant species. Invasive alien plants (IAP) may exist at various invasion degrees across a gradient of the colonization process with several grades of relative abundances in the occupied environments. The progressive variation in the invasion degree of IAP has the potential to modify their RA strategy. This study purposes of estimating the RA strategy of the IAP Solidago canadensis L. and the correlations among RA of S. canadensis, the invasion intensity of S. canadensis, the invasiveness of S. canadensis, and the community invasibility across a gradient of invasion degrees by using the field sampling experiment. The height and relative abundance of S. canadensis did not remarkably affect its RA. The RA of S. canadensis was positively related to its reproductive biomass and total biomass. The key reason may be that plant individuals with higher total biomass can allocate more resources into sexual reproduction. The RA of S. canadensis was positively related to its invasiveness. Thus, the RA of S. canadensis may be crucial to its invasiveness. Abstract : Height of Solidago canadensis does not affect its reproductive allocation (RA). Relative abundance of S. canadensis does not affect its RA. RA of S. canadensis is positively related to its invasiveness. Community stability declines with a rising invasion degree. Community invasibility raises with a rising invasion degree.